Decision Analysis Framing and Motivation Application in Business and Tourism (European Journal of Marketing and Economics, 2025)
This article examines the implications of framing in decision analysis and proposes a tool under rationality that incorporates attributes of behavioral models.  The proposed approach suggests that decision agents make an overall assessment of their state-conditional alternatives in association with exogenous environmental and social factors, resulting in an overall score of urgency that can be considered as the resource pool of motivation.  The process is formulated as a state-contingent input-requirement set and it is able to explain behavioral biases such as the certainty and pseudo-certainty effects, issues of Knightian uncertainty, risk management and innovation.  A Data Envelopment Analysis (DEA) formulation is also presented and an application of case analysis on business and tourism.
Keywords: decision, analysis, framing, motivation, application, business, tourism